Evaluasi Pelaksanaan Tugas Ketua Rukun Tetangga Dalam Membantu Tugas Kepala Desa Sungai Asam Kecamatan Belat Kabupaten Karimun - Muhamad Asrizal; Deska Zulkarnain (UIR Press, 2020)
Government policy in order to assist the task of the Kelurahan / Desa to improve service and population administration, the government has issued a Rukun Tetangga policy as an extension of the Kelurahan / Desa. Based on the policies that have been issued by the government, for this reason, researchers make an approach and offer to these policies by evaluating existing policies. This study aims to identify and analyze the evaluation of the implementation of the duties of the head of the Rukun Tetangga in helping the village head of Sungai Asam, Karimun Regency and also to identify and analyze the obstacles to the implementation of the duties of the Head of the Rukun Tetangga in Assisting the Task Implementation of the Head of the Rukun Tetangga in Helping the Task of the Village Head. Sungai Asam, Karimun Regency.